The Effectiveness of Deprivation of Voting Rights as an Additional Punishment Against Perpetrators of Corruption Crimes - Bayu Agung Pratama (Fox Justi : Jurnal Ilmu Hukum, 2025)
This study examines the effectiveness of revocation of voting rights as a form of additional punishment that can be imposed on perpetrators of corruption in the Indonesian criminal justice system. Corruption has become an extraordinary crime that causes state losses and hampers national development. Through a normative juridical approach with doctrinal research methods, this research analyzes the legal basis, implementation, and implications of revocation of voting rights as an alternative punishment to provide a deterrent effect. The results show that the revocation of voting rights as stipulated in Article 10 letter b of the Criminal Code in conjunction with Article 35 paragraph (1) number 3 of the Criminal Code and Article 18 paragraph (1) letter d of Law Number 31 Year 1999 jo. Law Number 20 Year 2001 on the Eradication of Corruption has a strong juridical basis, but its implementation is still limited. This research finds that the revocation of voting rights can be effective if applied consistently by considering proportionality and rehabilitative aspects. Challenges in its implementation include the absence of an effective monitoring mechanism and resistance from various parties. This study recommends the need to strengthen regulations on execution and supervision mechanisms, formulate clear sentencing guidelines, and harmonize regulations related to revocation of voting rights with election and human rights laws to increase the effectiveness of revocation of voting rights as a comprehensive corruption eradication effort.